Study of modern state of quality control hydraulic liquids - Соловйов, А.М.; Нетреба, Ж.М.; Кузнєцова, О.Я. (Proceedings of National Aviation University (archive), 2006)
In the work present of investigation results of the state control quality system of hydraulic liquids in the contemporary modem conditions of the consumption and storage. To present the results of investigation of change hydraulic liquids quality in the exploitation aviations technical. Propose the directions the perfection of the control quality liquids for hydraulic system aircraft.